Pet dog bites in children: management and prevention - Carri Westgarth; Molly Jakeman; James A Oxley; Sara C Owczarczak-Garstecka (BMJ Publishing Group, 2020)
Dog bite injuries are a significant public health problem and many are sustained by children. These injuries can be complex, both physically and psychologically, and in rare cases fatal. This paper will review current evidence-based approaches to treatment, explore identified patterns in biting incidents and discuss the effectiveness of prevention strategies. Safe management of these patients requires a comprehensive approach. Physical injuries need to be accurately assessed with a high index of suspicion for underlying injuries, particularly in younger children less able to communicate. Treatment depends on severity and location, but all bites must be irrigated to reduce the risk of infection but may not always require prophylactic antibiotic use. Careful exploration of the circumstances in which the bite occurred is essential to make safeguarding decisions and prevent future bites. Reducing the incidence of paediatric dog bites requires education of both children and parents that any dog can bite, regardless of breed, and all child-dog interactions must be highly supervised. However, education alone is unlikely to prevent dog bites. Policies that support environmental changes need to be developed such as provision of pet dogs less likely to bite (or bite as severely), through breeding for temperament and appropriate socialisation. Additionally, investment in psychological support for bite victims and their families is required to reduce the long-term impacts of being bitten.